Friend or foe? Co-opetition and entrepreneurial networking - Peter-J. Jost (Small Business Economics, 2021)
We study the formation of an entrepreneurial network in an environment, in which entrepreneurs who are contesting with each other for the development of a new venture have the possibility to collaborate. On the one hand, such bilateral knowledge collaborations are beneficial because they allow the integration of external knowledge. On the other hand, external knowledge collaborations reduce an entrepreneur's incentive to invest in her internal knowledge. We analyze this trade-off and show that if the knowledge transfer between collaborating partners is complete, the only stable entrepreneurial network is one with exactly one collaboration of each entrepreneur. If, however, knowledge transfers are only partial, entrepreneurial networking becomes more important and entrepreneurs form more knowledge collaborations. Moreover, internal or external knowledge spillovers reduce the incentives to form knowledge collaboration. These results have several practical implication for entrepreneurs and managers of small- and medium-sized enterprises (SMEs) in their pursuit to better understand factors that influence knowledge collaborations with competitors and to devise their co-opetition strategy.
Keywords: C72; D72; D74; L26; 330; Co-opetition; Entrepreneurial networking; Knowledge collaboration; Knowledge spillover